Pembuatan serta Pengembangan Sistem Informasi dan Whatshapp Bot sebagai Pelayanan Agrowisata Berbasis Web di Desa Pasung - Wajar Novianto; Handaru Jati (Journal of Information Technology and Education (JITED), 2024)
This study aims to: (1) Implement a website-based information system and whatsapp bot to expand existing information with the Wordpress content management system (CMS). (2) Guarantee the ease and function of using the website and whatsapp chatbot by testing the function using the functional suitability test and testing the ease of use using the usability test. The method used is Research and Development (R&D) with the Prototype model software development procedure. The prototype model consists of the communication stage, the quick plan & modeling quick design stage, the construction of prototype stage, and the deployment, delivery, and feedback stage. The results of this study are: (1) The pasungbersatu.com website was developed using a prototype model using the wordpress framework. (2) The results of testing the functional suitability aspect get a value of 100%, which means that all menu functions that are made are running well and are "Very Eligible" to be used. (3) The results of testing the usability aspect, namely the website is accepted by users, Grade Scale is C, Adjective Rating is good, and SUS percentile rank gets grade C, which means the pasungbersatu.com website is easy to use.